Lack of association between feline AB blood groups and retroviral status: a multicenter, multicountry study. Issue 8 (August 2022) - Spada, Eva; Jung, Hyein; Proverbio, Daniela; Perego, Roberta; Baggiani, Luciana; Ciuti, Silvia; Sharp, Claire R; Nash, Katherine J; Westman, Mark; Lait, Philippa JP; Davidow, Elizabeth B
Objectives: The relationship between blood group antigens and disease has been studied in humans. Blood types have been associated with both decreased and increased rates of various infections. In addition, blood group expression has been shown to vary with some cancers and gastrointestinal diseases. The objective of this study was to explore whether there is a relationship between blood type and retroviral infections in cats. Methods: Case records from a veterinary research laboratory, veterinary teaching hospitals and veterinary blood banks were retrospectively searched for cats where both blood type and retroviral status (feline leukemia [FeLV], feline immunodeficiency virus [FIV] or both) were listed (part 1). In addition, a sample of 33 cats with confirmed FIV infection was genotyped to determine blood groups (part 2). Results: In part 1, 709 cats were identified, 119 of which were positive for retroviral infection. Among all cases, 621 were type A (87.6%), 68 were type B (9.6%) and 20 were type AB (2.8%). There was no relationship between overall retroviral status (positive/negative) and blood type ( P  = 0.43), between FeLV status and blood type ( P  = 0.86) or between FIV status and blood type ( P  = 0.94). There was no difference in the distribution of blood types between cats that were healthy and typed as possible blood donors vs sick cats that were typed prior to a possible transfusion ( P  = 0.13). In part 2, of the 33 FIV-infected cats, all blood group genotypes were identified, although this test did not discriminate type A from type AB. Conclusions and relevance: No relationship was identified between feline retroviral status and blood type in this study. The relationship between blood type and other disease states requires further study in veterinary patients.